2014
DOI: 10.1002/jbm.b.33192
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of helicoidal multilamellar arginine-glycine-aspartic acid-functionalized silk biomaterials in a rabbit corneal model

Abstract: Silk proteins represent a unique choice in the selection of biomaterials that can be used for corneal tissue engineering and regenerative medical applications. We implanted helicoidal multilamellar arginine-glycine-aspartic acid-functionalized silk biomaterials into the corneal stroma of rabbits, and evaluated its biocompatibility. The corneal tissue was examined after routine hematoxylin-eosin staining, immunofluorescence for collagen I and III, and fibronectin, and scanning electron microscopy. The silk film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The 3D silk‐based construct we developed has acceptable optical transparency, favorable mechanical strength, and excellent cell biocompatibility, which are the essential properties of an ideal corneal equivalent. It has been reported that patterned silk fibroin film has suitable biocompatibility with the corneal stroma in rabbit . More work needs to be done, including in vivo biocompatibility tests and in situ animal studies to evaluate the potential of this 3D silk‐based construct as a transplant biomaterial for cornea repair.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D silk‐based construct we developed has acceptable optical transparency, favorable mechanical strength, and excellent cell biocompatibility, which are the essential properties of an ideal corneal equivalent. It has been reported that patterned silk fibroin film has suitable biocompatibility with the corneal stroma in rabbit . More work needs to be done, including in vivo biocompatibility tests and in situ animal studies to evaluate the potential of this 3D silk‐based construct as a transplant biomaterial for cornea repair.…”
Section: Resultsmentioning
confidence: 99%
“…Transplantation with human cadaveric tissue is presently the only treatment option in most cases, but severe tissue shortage has led to an urgent need to develop bioengineered alternatives to donor corneal tissue [2][3][4][5][6][7][8][9][10][11][12]. Natural collagen-derived corneal scaffolds are the most mature of these [13][14][15][16][17][18][19], and we recently reported results from collagen-based scaffolds four years after implantation into diseased human corneas [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the materials need to sustain the tissue biological functions, therefore supporting cellular growth and organization in 3D, while being implantable in the target site. Silk can be successfully used to answer corneal tissue needs, due to its mechanical and optical properties, its ability to support corneal cell growth and it is well tolerated when implanted intra-stromally [20, 37, 41]. The current biomaterial alternatives mainly rely on nano-fibrillar polyester, natural polymers blended polyethylene glycol and polylactic acid composites, as well as a variety of collagen-based constructs [18, 5357].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silk films have been shown to be a suitable materials for corneal stroma reconstruction in a rabbit animal model [41]. Silk films can be further organized in a 3D multi-lamellar architecture for the growth of corneal stromal cells, by optimizing topography, surface chemistry, and the porosity of each layer [37].…”
Section: Introductionmentioning
confidence: 99%